Language Ambiguity and Emotional Barriers: Semantic and Psychological Approaches in Interpersonal Communication - Ari Oldwin Sitorus; Lahmuddin Lubis (Badan Penerbit STIEPARI Press, 2025)
This study aims to analyze interpersonal communication barriers caused by language ambiguity and emotional barriers, especially in the context of today's digital communication and social interactions. Semantic ambiguity occurs when a word or sentence has more than one meaning that allows for misinterpretation, while emotional barriers include psychological conditions such as stress, anxiety, and anger that affect how messages are received and interpreted. This research approach uses a qualitative descriptive-analytical method that allows for in-depth exploration of the meaning, dynamics, and factors that influence interpersonal communication. Data analysis was carried out thematically with a hermeneutic approach to understand the relationship of meaning in social and psychological contexts. Semantic Ambiguity Theory by Stephen C. Levinson is the main foundation in understanding the disturbance of meaning in verbal communication, which emphasizes the importance of situational context and shared knowledge between communicators. The results of the study indicate that language ambiguity is increasingly common, especially in the communication of the younger generation who often use informal language, abbreviations, and digital symbols, so that it has the potential to cause conflict when combined with emotional barriers experienced by the recipient of the message. The close relationship between semantic ambiguity and psychological barriers worsens the effectiveness of interpersonal communication, especially in the workplace, education, and social media. Therefore, this study emphasizes the need for an interdisciplinary approach that combines semantic and psychological studies so that communication strategies can be more adaptive, reflective, and humane in dealing with the complexity of contemporary communication